Xylitol bioproduction: state-of-the-art, industrial paradigm shift, and opportunities for integrated biorefineries. (3rd October 2019) - Felipe Hernández-Pérez, Andrés; de Arruda, Priscila Vaz; Sene, Luciane; da Silva, Silvio Silvério; Kumar Chandel, Anuj; de Almeida Felipe, Maria das Graças
Abstract: Recent advances in biomass conversion technologies have shown a promising future toward fermentation during xylitol production. Xylitol is one of the top 12 renewable added-value chemicals that can be obtained from biomass according to US Department of Energy (USDOE). Currently, xylitol accounts for approximately US823.6 million of annual sales in the market, and this amount is expected to reach US1.37 billion by 2025. This high demand has been achieved owing to the chemical conversion of hemicellulosic hydrolysates from different lignocellulosic biomasses, which is a costly and non-ecofriendly process. Xylose-rich hemicellulosic hydrolysates are the major raw materials for xylitol production through either chemical or biotechnological routes. Economic production of a clean hemicellulosic hydrolysate is one of the major bottlenecks for xylitol production on the commercial scale. Advancements in biotechnology, such as the isolation of novel microorganisms, genetic manipulation of xylose metabolizing strains, and modifications in the fermentation process, can enhance the economic feasibility of xylitol production on the large scale. Furthermore, xylitol production in integrated biorefineries can be even more economic, given the readily available raw materials and the co-use of steam, electricity, and water, among others. Exploring new biotechnology techniques in integrated biorefineries would open new markets and opportunities for sustainable xylitol production to fulfill the market's growing demands for this sugar alcohol. This article is a review of the advancements reported in the whole biotechnological process for xylitol production, and involve pretreatment technologies, hemicellulosic hydrolysate preparation, xylose conversion into xylitol, and product recovery. Special attention is devoted to current metabolic engineering strategies to improve this bioprocess, as well as to the importance of xylitol production processes in biorefineries.